P375 Inflammatory cutaneous lesions in inflammatory bowel disease treated with vedolizumab or ustekinumab: an ECCO CONFER multi-centre case series. (25th January 2019) - Phillips, F M; Verstockt, B; Sebastian, S; Ribaldone, D G; Vavricka, S; Konstantinos, K; Slattery, E; de Suray, N; Flores, C; Fries, W; Vincenzi, F; Capoferro, E; et al.
Abstract: Background: Inflammatory cutaneous lesions are a common extraintestinal manifestation of inflammatory bowel disease (IBD). However, it is unknown whether such lesions, which may be refractory to standard medical therapy including anti-TNFs, would respond to the newer biologic agents ustekinumab (UST) or vedolizumab (VDZ). Methods: This was a European Crohn's and Colitis Organisation (ECCO) retrospective multi-centre case series, performed as part of the CONFER project. A call to all ECCO members was made to report on cutaneous lesions in IBD treated by UST or VDZ, excluding psoriasiform lesions. Clinical data were recorded in a standardised data collection form. Results: This report includes 28 patients with cutaneous lesions form 14 centres; 23 had Crohn's disease and 5 had ulcerative colitis whilst 19 were treated with UST and 11 with VDZ (2 patients were treated with both). All had failed immunomodulators and anti-TNF therapy. Metastatic Crohn's disease (MCD) was diagnosed in 10 patients (9 confirmed by histology) and UST therapy led to remission in 5 cases and partial response in 4 cases, with a single report of VDZ inducing remission. All cases of MCD that were treated with UST responded after the first or second dose, whilst for the 5 cases that attained remission, the median time for this was 5 months. Pyoderma gangrenosum (PG) was diagnosed in 4 cases; 3 of these attained remission with UST (median time to remission 4 months) whilst one case did not respond to VDZ. There were 7 cases of erythema nodosum (EN); UST led to remission in 4 cases and partial response in 1 case whilst VDZ had partial response in 2 cases and non-response in 2 cases. There were 7 single cases of other inflammatory lesions, which included: a case of leukoclastic vasculitis that attained remission with VDZ, a case of hidradenitis suppurotiva (HS) with partial response to UST, a case of dissecting cellulitis of the scalp that did not respond to UST; 2 unspecified cases with partial response to VDZ and another two unspecified cases with no response to VDZ. Conclusions: This is the first case series to describe the efficacy of UST and VDZ in the treatment of cutaneous lesions related to IBD. UST led to a remission or a partial response in all cases of MCD, PG, HS and EN. VDZ caused a partial response or non-response in EN and other inflammatory lesions, as well as a single case of remission in MCD.